Amnesties: conditio sine qua non for a Lasting Peace Solution or Ticking Time Bomb for Peacebuilding? - Agnieszka Szpak (Polish Political Science Yearbook, 2018)
The author attempts to define amnesty and describe conditions that must be met for amnesties to be in accordance with international law. This in turn involves an analysis of legality of amnesties. The paper also examines motivation for granting amnesty and desirability as well as the future of granting amnesties. In the end a nuanced approach is adopted highlighting the fact that amnesties are neither conditio sine qua non for a lasting peace solution nor ticking time-bombs for peacebuilding. This reflects the idea of this paper that justice is not an absolute and sometimes it might be necessary to let go and combine judicial and non-judicial mechanisms (including the disclosure of truth and reparations for the victims) in order to achieve sustainable peace.